PENGARUH BRAND SALIENCE, BRAND IMAGE, DAN BRAND TRUST TERHADAP KEPUTUSAN PEMBELIAN PRODUK AMDK MEREK AQUA DI KABUPATEN SIDOARJO - Muhammad Sonhaji; Alshaf Pebrianggara; Muhammad Yani (MANAJEMEN DEWANTARA, 2026)
This study examines the effects of brand salience, brand image, and brand trust on purchase decisions of AQUA bottled drinking water among Generation Z consumers in Sidoarjo Regency. Understanding brand-related determinants of purchase decisions is essential amid increasing competition in the bottled water industry and changing consumer behavior among younger generations. This research adopts a quantitative approach using a survey method. Data were collected from 96 Generation Z consumers who had purchased AQUA bottled water, selected through purposive sampling. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 3 to evaluate both the measurement and structural models. The findings reveal that brand salience and brand trust have a positive and significant effect on purchase decisions, while brand image does not exhibit a significant influence. Brand trust shows the strongest effect, indicating its critical role in shaping consumer purchase decisions. These results highlight the importance of strengthening consumer trust to enhance purchasing behavior in the bottled drinking water market.